Estimation of Welfare Effects in Hedonic Difference-in-Differences: The Case in School Redistricting - Xiaozhou Ding; Christopher Bollinger; Michael Clark; William Hoyt; William H. Hoyt (Center for Economic Studies and ifo Institute (CESifo), 2023)
The difference-in-differences (DID) approach that identifies the capitalization of amenities through changes in housing prices has been widely used in the literature of hedonic estimation in the past decade. However, concerns have been raised about how to interpret the estimated capitalization effects as changes in welfare. Following an approach developed by Banzhaf (2021), we estimate the capitalization of school redistricting in a generalized DID framework that incorporates general equilibrium effects. When comparing estimates from our generalized DID model to the conventional DID model, we find significant differences in both the capitalization effects and welfare changes associated with the school redistricting.
Keywords: H40; I20; R20; 330; difference-in-differences; hedonics; welfare; school quality